Clinical aspects of hydatidiform mole. - Bachmann Sánchez, Carlos (2015)
We will deal with the clinical aspects of trophoblastic disease, specifically the hydatidiform mole, because we have seen that within the mole trophoblast disease is much more common than choriocarcinoma. We rely on studies carried out by Wynn in making comparisons between the ultrastructure of hydatidiform mole with a normal placenta and trophoblastic malignancy.